THE ANALYSIS OF CONSUMER BEHAVIOR TOWARDS UMRAH AND HAJI TRAVEL PACKAGES OF PT. ASRI WISATA INDONESIA - Pratiwi, Ardila; Seny Luhriyani; Andi Hajar; Andi Riswan Mohamad (International Journal of Business English and Communication, 2024)
This study aims to find out what are the reasons people choose PT. Asri Wisata Indonesia as a means to the holy land and how PT. Asri Wisata Indonesia advertises its company so that people are interested. This study used descriptive qualitative method. Data collection techniques using interview guideline research instruments. The subjects of this research are the customers of PT. Asri Wisata Indonesia and also employees from PT. Asri Wisata Indonesia with five customers and one employee randomly selected. And the results of the interviews show that most of the people choose PT. Asri Wisata Indonesia from an acquaintance, exhibition, distribution of vouchers, and social media. So it can be concluded that PT. Asri Wisata Indonesia is very good at distributing company packages to attract a customer to become a loyal member of PT. Asri Wisata Indonesia.